Pressure injuries in surgical patients: a comparison of Norton, Braden and Waterlow risk assessment scales - GÜRKAN, AYSEL; KIRTIL, İNCİ; DİKMEN AYDIN, YEŞİM (My University, 2022)
Objective: This study aims to determine the predictive power of the Norton, Braden and Waterlow scales in determining risk of pressure injury (PI) in surgical patients.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Dermatoloji; Medicine; Health Sciences; Internal Medicine Sciences; Dermatology; DERMATOLOJİ; Klinik Tıp; Klinik Tıp (MED); DERMATOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Braden; Norton; predictive capacity; predictive validity; pressure injury; pressure ulcer; risk assessment; scales; ulcer; Waterlow; wound; wound care; wound healing; ULCER RISK; PREDICTIVE-VALIDITY; PREVENTION; PREVALENCE; LONG